Syrian refugees' experiences with mental health services in Turkey: "I felt lonely because I wasn't able to speak to anyone". Issue 4 (15th May 2019) - Doğan, Nareg; Dikeç, Gül; Uygun, Ersin
Abstract: Purpose: This study examined Syrian refugee adults' experiences with mental health services due to a mental complaint. Design and Methods: This qualitative study used a phenomenological design. The data were collected in semi‐structured focus group interviews between June and August 2018. A total of 24 individuals participated in the study. The data were analyzed using Colaizzi's method of phenomenological interpretation. Findings: Seven themes were identified by thematic analysis of the interviews: (a) difficulties making appointments, (b) difficulties obtaining medicine, (c) personal rights, (d) lack of information, (e) language barrier, (f) discrimination, and (g) confidence versus anxiety. Practice Implications: Nurses should be aware of the barriers experienced by refugees that affect the quality and accessibility of psychiatric services.